3-Month Injection Contraception And Obesity In Puskesmas Banding Agung - Kholilah Kholilah; Luluk Yuliati; Irfana Tri Wijayanti (Journal of Midwifery and Nursing, 2023)
The 3-month injectable contraception is a highly effective method of hormonal contraception that prevents pregnancy. However, some acceptors may experience side effects, such as weight gain. This research aims to determine the relationship between the duration of 3 months of injectable contraceptive use and the incidence of obesity at the Health Center of Banding Agung. The study used a correlational analytic method with a cross-sectional approach. The population consisted of all mothers who had used the 3-month injection contraception for three months, with a total of 1,250 acceptors. The sample size was 93 respondents, and measuring tools used were family planning visit books, medical records, scales, and height measuring devices (GEA brand). The study found that those who used the 3-month injection contraception for over two years had the same number of obese people, namely 74 respondents (79.6%). The Fisher's Exact test obtained a p-value of <0.001 (? = 0.05), indicating a long-term relationship between 3-month injection contraception and obesity at the Banding Agung Inpatient Health Center. Understanding this link and providing proper services and education can help women make informed contraceptive decisions for their well-being.